PENINGKATAN KOMPETENSI TEKNIK DAN KEWIRAUSAHAAN SISWA SMK PERTANIAN UNTUK MEMPERSIAPKAN TENAGA KERJA DI ERA PERTANIAN DIGITAL - Rita Hayati; Yukiman Armadi (CV. ADIBA AISHA AMIRA, 2025)
The transformation of agriculture towards the digital era requires human resources with technical and entrepreneurial competencies relevant to the needs of modern industry. This study aims to analyse how improving technical and entrepreneurial competencies can prepare agricultural vocational school students to meet the demands of work in the digital agriculture sector. Using a descriptive qualitative approach, data was obtained through interviews, learning observations, and document studies related to the implementation of vocational competency strengthening. The results showed that technical competencies, including mastery of sensor-based agricultural technology, IoT, modern mechanisation, and digital literacy, contributed significantly to improving students' work readiness. On the other hand, entrepreneurial competencies enhance creativity, the ability to identify agribusiness opportunities, and students' motivation to pursue a career in the modern agricultural sector. The integration of these two competencies has been proven to strengthen students' interest in agriculture while shaping their adaptive abilities in facing the dynamics of digital agriculture. This study emphasises the importance of curriculum renewal, teacher capacity building, the provision of modern practical facilities, and partnerships with industry to support the development of students' competencies as future agricultural workers.